Performance evaluation of semantic based service selection methods. (October 2018) - Maheswari, S.; Karpagam, G.R.
Abstract: Web service is a functionality which is accessed through the internet. Different service providers offer same functionality which has increased the efficiency of service to a great amount.The customers have to access by selecting web services.The goal is to find the appropriate web services that fulfill the customer requirements. Service selection is the process of selecting the most suitable service from the list of discovered services. This process is usually based on the metrics like Quality of Services(QoS) and are ranked based on the QoS values using four service selection techniques namely Analytic Hierarchy Process (AHP), Logic Scoring Preference (LSP), Fuzzy Technique for Order of Preference by Similarity to Ideal Solution (Fuzzy Topsis) and Web service relevancy factor (WsRF). Inappropriate service selection leads to many complications which in turn require an evaluation scheme for adopting a distinct method. The performance evaluation of the service selection methods is carried out using analysis of variance (ANOVA). To improve the performance of service selection, the Iterative MapReduce is used. This reduces the execution time of the each selection process by running the process parallel.